PENGUJIAN KARAKTERISTIK FUNCTIONAL SUITABLITY DAN PERFORMANCE EFFICIENCY APLIKASI AUGMENTED REALITY MENGENAL TOKOH WAYANG SASAK - Ari Rudiyan; Ema Utami; Dhani Ariatmanto (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
An application product is said to be of quality if it meets the standards required by an internationally agreed organization. ISO 25010 is an international organization that issues standards to measure the suitability quality of an application or software developed by individuals or organizations. Getting to Know Wayang Sasak Characters is a software product designed as an Android-based augmented reality application. Therefore, the application Getting to Know Sasak Wayang Figures needs to be evaluated to determine its quality and suitability. This article aims to convey two test results of the characteristics contained in ISO 25010, namely functional suitability and performance efficiency. Functional suitability characteristics were tested using the black box method. The data collection technique was carried out using test cases. The results of the test case data processing are then calculated using the feature completeness matrix. Next, for performance efficiency characteristics, calculate the distance of the marker to the smartphone camera with the help of a ruler. Next, to find out the performance during the initial launch of the application, use the Firebase Lab Test tool. Test results for functional suitability characteristics, based on the feature completeness matrix, obtained a result of X = 0.87. These results show that the Getting to Know Sasak Wayang Characters application can run optimally even though there are still several features that are not functioning as expected. The results of performance efficiency testing by measuring market distance can detect markers up to 80 cm. The initial launch time for the application was obtained in 45 seconds using the Firebase Lab tools. The results of this research can then be used as a reference for developing the Getting to Know Sasak Wayang Characters application.